Self-discharge of supercapacitors based on carbon nanosheets with different pore structures - Zhao, Man; Shi, Mingwei; Zhou, Huanhuan; Zhang, Zailei; Yang, Wei; Ma, Qun; Lu, Xianmao (Electrochimica Acta, 2021)
Self-discharge is an important factor to be considered for practical applications of supercapacitors (SCs). While the transport of electrolyte ions largely determines the rate performance of SCs, it also affects their self-discharge rate. In this work, three carbon materials, namely stacking carbon nanosheets (S-CNSs), double-layer carbon nanosheets (DL-CNSs), and flower-like carbon nanosheets (FL-CNSs), with similar pore sizes but different pore structures were synthesized. Due to the different pore structures and cor- respondingly different ion transport resistances, the rate performances increased from S-CNS, FL-CNS, to DL-CNS SCs. On the other hand, the self-discharge rates increased following the same order –the open circuit voltage dropped from 2.0 to 0.99, 0.74, and 0.53 V after 24 h for S-CNS, FL-CNS, and DL-CNS SCs, respectively. Analysis of the self-discharge processes indicates a combined diffusion-controlled and ohmic leakage self-discharge mechanism and a larger diffusion constant was found for DL-CNS than that of FL- CNS and S-CNS SCs, consistent with their order of self-discharge rates. The results of this work suggest that although fast ion transport is beneficial to the rate performance of SCs, it may also lead to fast self-discharge and limit the duration of energy storage<br
Keywords: Carbon nanosheets; Self-discharge; Diffusion-controlled mechanism; Ohmic leakage; Rate performance